Prevalence of risk factors associated with hypertension at Sanglah General Hospital, Bali - Mahen Isaac Pannir Chelvam; I Wayan Sugiritama; I Gusti Nyoman Kamasan Arijana (Intisari Sains Medis, 2020)
Background: High blood pressure, also called "hypertension," is a serious medical condition. It happens when the force of the blood pumping through the arteries is too strong. The World Health Organization rates hypertension as one of the most important causes of premature death worldwide, and the problem is growing. This study aimed to determine the risk factors affecting Hypertension at Sanglah general hospital.Methods: This study was a descriptive study with a cross-sectional approach. The data used in this study is a secondary data collected from medical record of the patients with Hypertension at Sanglah general hospital, Denpasar, Bali in the year of 2015 until 2016. The data was categorized based on Body Mass Index (BMI), gender, age, alcohol consumption, and history of cardiovascular diseases.Results: There are 73(60.83%) males and 47(39.17%) females, the majority of patients were in the age group of 18 – 70 years of age with the age group of 40 - 50 carrying a rather large quantity of 45.8% among the male gender and for the female gender the age group of 51 – 60 showed the highest percentage of 38.2%, the sample consists of 60.83% of males and 39.17 of females from the total 120 samples taken from Sanglah general hospital. As for Body Mass Index (BMI), 25 – 29.9 has the most significant value of 49 (40.83%) when compared to the other nutritional statuses present. The patients with the cardiovascular disease showed a very substantial amount of 69 (57.5%) among males and 41 (34.17%) among females. Patients with a history of alcohol consumption for the male gender had a value of 34 (28.30%), and for the female gender group, it carried an amount of 2 (1.70%).Conclusions: This study succeeded in identifying 120 samples of patients with hypertension and their contributing risk factors. The majority of the Samples were with body mass index (BMI) 25 – 29.9 (40.83%). The samples with a history of cardiovascular disease showed a value of 69 (57.5%) among males and 41 (34.17%) among females. Patients with a history of alcohol consumption for the male gender had a value of 34 (28.30%), and for the female gender group, it carried an amount of 2 (1.70%)